DNA methylation pattern is determined by the intracellular level of the methylase. - Szyf, M (1984)
Extrachromosomal plasmid DNA is transiently undermethylated in Escherichia coli during amplification in the presence of chloramphenicol. In addition, undermethylation of phage lambda DNA was observed after thermal induction of a lambda c1857 lysogen while the integrated lambda phage DNA was found to be fully methylated. These methylation pattern changes occur under conditions (extensive replication) in which the intracellular methylase level becomes limiting. In an E. coli strain that harbors a plasmid that carries the dam methylase gene and therefore overproduces dam methylase, there is no undermethylation of dam sites in either of the extrachromosomal DNAs. The sites that are methylated by the mec methylase in both plasmid and lambda phage DNAs were undermethylated in the dam overproducer as well. These results indicate that the intracellular level of the E. coli methylase determines the DNA methylation pattern.